Current Use of Gait Belt in Hospitals of Certain Areas in China - LUO Mi; YUE Guang; MU Keli (康复学报)
ObjectiveTo investigate the current status of gait belt use in the hospitals in China and to explore the factors that are related to the decision-making of Chinese rehabilitation practitioners.MethodsSurvey method was used in the study. A survey questionnaire was developed and distributed through the social media Wechat. SPSS 24.0 software was used to complete the statistical analyses.ResultsA total of 378 questionnaires were returned. The results showed that most participants had never heard about gait belt (64.0%). The awareness of gait belt was significantly associated with the professions of the participants (P=0.038). The resources in which participants learned about gait belt were mainly textbooks, journals, internships, friends, coworkers, and the internet. Among the 136 participants who had heard about gait belt, forty-seven (34.6%) of them reported the reason for using gait belt was because it was convenient, safe, and energy saving. Most of the participants didn't use it on patients (65.4%) even though they knew about gait belt. Almost all the participants who did not know gait belts voiced that they were willing to use it once they understand the benefits of gait belt use and ways to use it correctly (92.2%).ConclusionGait belt is not widely known and used by the participants. Rehabilitation practitioners' knowledge of gait belt is the most important factor that is related to the use of gait belt in China. To advocate gait belt use, awareness and education of gait belt should be considered as the first step which can be implemented in various ways, such as required content in the professional school curriculum, in continued education and review of pertinent literature. At the same time, the access to gait belt, which can be facilitated by the leaders in healthcare facilities, would contribute to this advocacy remarkably.